Pengaruh Fraud Diamond, Religiusitas dan Love Of Money Terhadap Kecurangan Akademik Mahasiswa Fakultas Ekonomi dan Bisnis Universitas Islam Malang Selama Pandemi Covid-19 - Duwi Pebrianti Ambarsari; Noor Shodiq Askandar; Abdul Wahid Mahsuni (e_Jurnal Ilmiah Riset Akuntansi, 2023)
This research was conducted at the Faculty of Economics and Business, Islamic University of Malang. The method used in this research is a quantitative method. The purpose of this study was to determine the effect of diamond fraud, religiosity and love of money on academic fraud. The independent variables used are diamond fraud, religiosity and love of money, the dependent variable is academic fraud. The sample used in this research was 90 respondents who were active students of the Faculty of Economics and Business in 2019 and 2020 who had attended online learning. Data collection techniques using a questionnaire. The analytical method used is instrument test, normality test, classical assumption test, multiple linear test, and hypothesis testing using SPSS computer software in data processing. The results of this study indicate that fraud diamond has no effect on academic fraud, religiosity has a negative effect on academic fraud, love of money has a positive effect on academic fraud, and simultaneously the variables fraud diamond, religiosity and love of money have a positive and significant effect on academic fraud.Keywords : Fraud diamond, religiosity, love of money, academic fraud.